2013
DOI: 10.4315/0362-028x.jfp-12-168
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of DNA Barcodes in Regulatory Science: Identification of the U.S. Food and Drug Administration's ``Dirty 22,'' Contributors to the Spread of Foodborne Pathogens

Abstract: The U.S. Food, Drug, and Cosmetic Act prohibits the distribution of food that is adulterated, and the regulatory mission of the U.S. Food and Drug Administration (FDA) is to enforce this Act. FDA field laboratories have identified the 22 most common pests that contribute to the spread of foodborne disease (the "Dirty 22"). The current method of detecting filth and extraneous material (tails, legs, carcasses, etc.) is visual inspection using microscopy. Because microscopy can be time-consuming and may yield in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Dunn et al 2010), fisheries inspection and trade (Costa and Carvalho 2007;Holmes et al 2009) and food safety (e.g. Jones et al 2013), being particularly useful when morphological characters are challenging for species diagnostic or when only parts of the specimens are available. In particular, DNA barcoding has proved to be a valuable tool in identifying marine organisms, and specifically chondrichthyan species (Spies et al 2006;Moura et al 2008b;Ward et al 2008;Wong et al 2009;Moftah et al 2011;Serra-Pereira et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dunn et al 2010), fisheries inspection and trade (Costa and Carvalho 2007;Holmes et al 2009) and food safety (e.g. Jones et al 2013), being particularly useful when morphological characters are challenging for species diagnostic or when only parts of the specimens are available. In particular, DNA barcoding has proved to be a valuable tool in identifying marine organisms, and specifically chondrichthyan species (Spies et al 2006;Moura et al 2008b;Ward et al 2008;Wong et al 2009;Moftah et al 2011;Serra-Pereira et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…US federal law makes use of the Daubert Standard to assess the validity of expert evidence (Berger 2011); some principles may be transferable. The US Food and Drug Administration (FDA) has also provided DNA barcode standards for their 22 major food-borne pest animals (Jones et al 2013).…”
Section: Standardization Of Identification Methodsmentioning
confidence: 99%
“…In both examples users must locate information published under both names, so databases should have both (ITIS n.d.; Guala 2016). However, sometimes what was thought to be a single species is discovered to comprise different entities, e.g., the red palm weevil comprising two species: Rhynchophorus ferrugineus (Olivier) and R. vulneratus (Panzer) (Rugman- Jones et al 2013), and biological and other observations recorded under the original name cannot with confidence be applied to one or other of the new concepts. Barcode ''provisional nomenclature'' to enable reference to informal concepts may be helpful (Schindel and Miller 2009).…”
Section: Taxonomic Name Managementmentioning
confidence: 99%
“…Handy et al (2011) reported a single-laboratory validated barcoding method for fish identification. Jones, Peters, Weland, Ivanova, and Yancy (2013) reported the use of DNA barcodes for identification of hazard animals in relation to filth in food. Our laboratory lately reported the application of plant DNA barcodes for small berry authentication (Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%